Development of titanium dioxide based compact layers and light scattering layers for enhanced dye-sensitized solar cell - Mustafa, Muhammad Norhaffis (2020)
Dye-sensitized solar cells (DSSCs) are the third-generation solar cell that capable of converting solar energy into electrical energy. Titanium dioxide (TiO2) as a photoanode has faced a lot of drawbacks such as low dye loading capacity, a small range of light scattering, high recombination effect and low charge transport ability that subsequently reduces its power conversion efficiency (PCE). In this work, the enhancement of DSSC performance was studied by the modification of photoanode, specifically on the fabrication of a new compact layer (CL) and light scattering layers (LSLs). A dense, compact and homogenous TiO2 CL was optimized and prepared using response surface methodology by central composite design (RSM/CCD) and heat treatment assisted electrospinning, respectively. The TiO2 CL was successfully optimized with less than 5% residual standard error (RSE) and capable of enhancing the PCE up to 76.88% compared with the bare photoanode (1.73%). This is due to an improved electron lifetime (τn) and charge collection efficiency (ηc), resulting in a low recombination effect that leads to a higher PCE. Two LSLs were prepared in this study, namely polyvinyl alcohol (PVA/TiO2) nanofibers and TiO2 decorated by graphene quantum dot (TiO2-GQD). The PVA/TiO2 was prepared using electrospinning while TiO2-GQD was prepared via electrodeposition and drop-casting technique. Both PVA/TiO2 nanofibers and TiO2-GQD LSLs were successfully optimized using RSM/CCD with less than 5% RSE. Upon the addition of TiO2-GQD LSL onto the photoanode, the PCE increased up to 5.01% compared to the photoanode with PVA/TiO2 nanofibers LSL (4.06%) and bare photoanode (3.06%). This increment is due to the longer τn, higher ηc, higher dye loading capacity and higher light reflectance, demonstrating a good light scattering material. Furthermore, a fully flexible photoanode with TiO2-GQD LSL has successfully fabricated on indium doped tin oxide/polyethylene naphthalate (ITO/PEN) flexible substrate via electrodeposition and drop-casting technique. The fully flexible DSSC device consisting of photoanode with TiO2-GQD LSL showed an enhanced PCE of 5.18% compared to the bare photoanode (2.65%). The vast enhancement of PCE was due to the increase in the dye loading capacity (more dye can be adsorbed) and light scattering ability (more light can be scattered) upon the addition of TiO2-GQD LSL. In a nutshell, the introduction of CL and LSLs has successfully increased the DSSC performance.